2020
DOI: 10.5483/bmbrep.2020.53.2.108
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Multidrug Resistance by Activating Unfolded Protein Response of the Endoplasmic Reticulum in Cisplatin-Resistant A2780/CisR Ovarian Cancer Cells

Abstract: Cisplatin is a widely used anti-cancer agent. However, the effectiveness of cisplatin has been limited by the commonly developed drug resistance. This study aimed to investigate the potential effects of endoplasmic reticulum (ER) stress to overcome drug resistance using the cisplatin-resistant A2780/CisR ovarian cancer cell model. The synthetic chalcone derivative (E)-3-(3,5-dimethoxyphenyl)-1-(2-methoxyphenyl)prop-2-en-1-one (named DPP23) is an ER stress inducer. We found that DPP23 triggered apoptosis in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In ovarian cancer cells, CP enhances ROS levels to induce ER stress. Then, UPR activates that overcomes drug resistance [101]. It seems that ROS levels can be considered as a biomarker for predicting response of cancer cells to chemotherapy.…”
Section: Ros Cisplatin Chemotherapy and Related Molecular Pathways Cisplatin Sensitivitymentioning
confidence: 99%
“…In ovarian cancer cells, CP enhances ROS levels to induce ER stress. Then, UPR activates that overcomes drug resistance [101]. It seems that ROS levels can be considered as a biomarker for predicting response of cancer cells to chemotherapy.…”
Section: Ros Cisplatin Chemotherapy and Related Molecular Pathways Cisplatin Sensitivitymentioning
confidence: 99%
“…Cisplatin is widely used as a clinical anticancer drug and has been reported as one of the most effective chemotherapeutic drugs for OC [ 30 , 31 ]. Choi et al confirmed that Scutellaria baicalensis combined with cisplatin has a synergistic anticancer effect on human OC cells [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the development of more effective and safer antitumor agents has become the focus of drug discovery. In general, natural products are advantageous due to the easy availability and relative safety, and chalcone derivatives have good cytotoxic activity towards several tumor cells(Tsai et al, 2014; Yan et al, 2016; Makhdoumi et al, 2017; Wang et al, 2018; Jung et al, 2019), which has led to the increasing consideration of chalcone derivatives as the anti-tumor treatment (Bommareddy et al, 2018; Kim and Kim, 2018). Based on the skeleton of chalcone, the hydrogens on the benzene ring were replaced by various substituents (electron-acceptor groups: –Br, –Cl, and –F; electron-donor groups: –OCH 3 , –CH 3 ) to explore the effects of electronegativity on the inhibitory activities of the compounds against the tumor cells.…”
Section: Discussionmentioning
confidence: 99%